“Towards the Application of Blockchain Technology for Improving Trade Facilitation in CEFTA 2006” - Mihajlov, Martin; Toshevska trpchevska, Katerina; Kikerkova, Irena (Sveuciliste u Dubrovniku, 2019)
The benefits and value drivers of customs digitalization are considerable. The key motivation is the efficiency associated with minimizing the cost of managing documents throughout the trade process, including costs associated with the exchange of documents with other countries, as well as the procurement and facilitation of those documents. Since it is of general knowledge that effective trade facilitation signifies reliability and security of the trade transactions we think that blockchain technology may be able to offer a high level of confidence in these areas to both traders and regulators. The proposal presented in this paper is focused on jointly moving all (customs) stakeholders towards a standardized integration of collaborative processes. By investigating blockchain solutions along with technology and standards, we propose a pathway to achieving an international system-to-system integration. Taking into consideration the realization of deeper integration among the countries, especially in the field of trade and digital integration, we try to analyze how blockchain technology can help support that integration. In order to analyze the possible application of this technology for deepening CEFTA integration through enhancing trade facilitation we briefly refer to its’ positive aspects. Instead of developing individual software solutions in CEFTA countries it might be beneficial to move services to a blockchain technology platform. While currently, this might be hindered by local policies, blockchain technology will have its’ influence and application in trade facilitation as it has in many other fields. With full awareness of the possible threats and challenges, it is of the utmost importance to engage in discovering the most compatible pathway to apply this technology in regional trade facilitation and deepen digital integration among CEFTA member countries.
Keywords: Trade facilitation, CEFTA-2002, Block-chain technology, positive aspects; deepening digital integration